Who's up to the challenge?18

Calculus Level 5

k = 1 n = 2 k 1 + 1 2 k k 2 n ( 2 n 1 ) \large \displaystyle\sum _{ k=1 }^{ \infty }{ \displaystyle\sum _{ n={ 2 }^{ k-1 }+1 }^{ { 2 }^{ k } }{ \frac { k }{ 2n(2n-1) } } }

If the value of the series above is equal to A B γ A-B\gamma , where A A and B B are positive integers, find A + B A+B .

Notation : γ \gamma denotes the Euler-Mascheroni constant .


This is a part of Who's up to the challenge?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Thomas Welle
Dec 6, 2019

Let's define: H n = k = 1 n 1 k = 1 + 1 2 + 1 3 + 1 4 + + 1 n H_n = \sum^{n}_{k=1} \frac{1}{k} = 1 + \frac{1}{2} + \frac{1}{3} + \frac{1}{4} + \dots + \frac{1}{n} A n = k = 1 n ( 1 ) k + 1 k = 1 1 2 + 1 3 1 4 + ± 1 n A_n = \sum^{n}_{k=1} \frac{(-1)^{k+1}}{k} = 1 - \frac{1}{2} + \frac{1}{3} - \frac{1}{4} + \dots \pm \frac{1}{n} For an even number 2 n 2n , A 2 n = 1 1 2 + 1 3 1 4 + 1 2 n = ( 1 + 1 2 + 1 3 + 1 4 + + 1 2 n ) 2 ( 1 2 + 1 6 + 1 8 + + 1 2 n ) = H 2 n H n A_{2n} = 1 - \frac{1}{2} + \frac{1}{3} - \frac{1}{4} + \dots - \frac{1}{2n} = \left(1 + \frac{1}{2} + \frac{1}{3} + \frac{1}{4} + \dots + \frac{1}{2n} \right) - 2\left( \frac{1}{2} + \frac{1}{6} + \frac{1}{8} + \dots + \frac{1}{2n} \right) = H_{2n} -H_{n} Also note that, lim n A n = 1 1 2 + 1 3 1 4 + = ln 2 \lim_{n \to \infty} A_{n} = 1 - \frac{1}{2} + \frac{1}{3} - \frac{1}{4} + \dots=\ln{2}

Now let's let S S denote the sum of this series. S = k = 1 n = 2 k 1 1 2 k k 2 n ( 2 n 1 ) S= \sum_{k=1}^{\infty} \sum_{n=2^{k-1} -1}^{2^k} \frac{k}{2n(2n-1)} The fraction 1 2 n ( 2 n 1 ) \frac{1}{2n(2n-1)} can be written as 1 2 n 1 1 2 n \frac{1}{2n-1}-\frac{1}{2n} . So, S = k = 1 k n = 2 k 1 1 2 k 1 2 n 1 1 2 n = 1 ( 1 3 1 4 ) + 2 ( 1 5 1 6 + 1 7 1 8 ) + 3 ( 1 9 1 10 + 1 11 1 12 + 1 13 1 14 + 1 15 1 16 ) + S= \sum_{k=1}^{\infty} k \sum_{n=2^{k-1} -1}^{2^k} \frac{1}{2n-1}-\frac{1}{2n} = 1\left(\frac{1}{3} -\frac{1}{4}\right) +2\left(\frac{1}{5} -\frac{1}{6} +\frac{1}{7} -\frac{1}{8}\right) + 3\left(\frac{1}{9} -\frac{1}{10}+\frac{1}{11} -\frac{1}{12}+\frac{1}{13} -\frac{1}{14}+\frac{1}{15} -\frac{1}{16}\right) +\dots Add the equation 0 = ln 2 ( 1 1 2 + 1 3 1 4 + ) 0=\ln2 - \left(1-\frac{1}{2} + \frac{1}{3} - \frac{1}{4} + \dots \right) . S = ln 2 ( 1 1 2 ) + 1 ( 1 5 1 6 + 1 7 1 8 ) + 2 ( 1 9 1 10 + 1 11 1 12 + 1 13 1 14 + 1 15 1 16 ) + S=\ln2 -\left(1-\frac{1}{2}\right) +1\left(\frac{1}{5} -\frac{1}{6} +\frac{1}{7} -\frac{1}{8}\right) + 2\left(\frac{1}{9} -\frac{1}{10}+\frac{1}{11} -\frac{1}{12}+\frac{1}{13} -\frac{1}{14}+\frac{1}{15} -\frac{1}{16}\right) +\dots Move ( 1 1 2 ) \left(1-\frac{1}{2}\right) to the left hand side, and we can see that we have reduced the coefficient on each of the terms by one. S + ( 1 1 2 ) = ln 2 + 1 ( 1 5 1 6 + 1 7 1 8 ) + 2 ( 1 9 1 10 + 1 11 1 12 + 1 13 1 14 + 1 15 1 16 ) + S +\left(1-\frac{1}{2}\right)=\ln2 +1\left(\frac{1}{5} -\frac{1}{6} +\frac{1}{7} -\frac{1}{8}\right) + 2\left(\frac{1}{9} -\frac{1}{10}+\frac{1}{11} -\frac{1}{12}+\frac{1}{13} -\frac{1}{14}+\frac{1}{15} -\frac{1}{16}\right) +\dots Let's repeat this. Add 0 = ln 2 ( 1 1 2 + 1 3 1 4 + ) 0=\ln2 - \left(1-\frac{1}{2} + \frac{1}{3} - \frac{1}{4} + \dots \right) . S + ( 1 1 2 ) = 2 ln 2 ( 1 1 2 + 1 3 1 4 ) + 1 ( 1 9 1 10 + 1 11 1 12 + 1 13 1 14 + 1 15 1 16 ) + S +\left(1-\frac{1}{2}\right)=2 \ln2 -\left(1 -\frac{1}{2} + \frac{1}{3} - \frac{1}{4} \right) + 1\left(\frac{1}{9} -\frac{1}{10}+\frac{1}{11} -\frac{1}{12}+\frac{1}{13} -\frac{1}{14}+\frac{1}{15} -\frac{1}{16}\right) +\dots S + ( 1 1 2 ) + ( 1 1 2 + 1 3 1 4 ) = 2 ln 2 + 1 ( 1 9 1 10 + 1 11 1 12 + 1 13 1 14 + 1 15 1 16 ) + S +\left(1-\frac{1}{2}\right) +\left(1 -\frac{1}{2} + \frac{1}{3} - \frac{1}{4} \right) =2 \ln2 + 1\left(\frac{1}{9} -\frac{1}{10}+\frac{1}{11} -\frac{1}{12}+\frac{1}{13} -\frac{1}{14}+\frac{1}{15} -\frac{1}{16}\right) +\dots If we repeat this procedure n times, we'll get: S + A 2 + A 4 + A 8 + + A 2 n = n ln 2 + 1 ( 1 2 n + 1 + 1 1 2 n + 1 + 2 + 1 2 n + 2 ) + 2 ( ) + S+A_2+A_4+A_8+\dots+A_{2^n}=n\ln2 +1\left(\frac{1}{2^{n+1}+1} -\frac{1}{2^{n+1}+2} +\dots -\frac{1}{2^{n+2}} \right) +2\left( \dots \right) + \dots One can convince oneself that the terms on the right of n ln 2 n \ln2 approach 0 in the limit of large n. What about the left hand side? Remember, A 2 n = H 2 n H n A_{2n} = H_{2n} -H_{n} . So we get: S + ( H 2 H 1 ) + ( H 4 H 2 ) + ( H 8 H 4 ) + + ( H 2 n H 2 n 1 ) = n ln 2 + 1 ( 1 2 n + 1 + 1 1 2 n + 1 + 2 + 1 2 n + 2 ) + S+(H_2-H_1) + (H_4-H_2) +(H_8 -H_4) + \dots+(H_{2^n} -H_{2^{n-1}})=n\ln2 +1\left(\frac{1}{2^{n+1}+1} -\frac{1}{2^{n+1}+2} +\dots -\frac{1}{2^{n+2}} \right) + \dots S H 1 + H 2 n = n ln 2 + 1 ( 1 2 n + 1 + 1 1 2 n + 1 + 2 + 1 2 n + 2 ) + S-H_1 +H_{2^n} =n\ln2+ 1\left(\frac{1}{2^{n+1}+1} -\frac{1}{2^{n+1}+2} +\dots -\frac{1}{2^{n+2}} \right) + \dots S = 1 + ln 2 n H 2 n + 1 ( 1 2 n + 1 + 1 1 2 n + 1 + 2 + 1 2 n + 2 ) + S=1 +\ln2^n -H_{2^n} + 1\left(\frac{1}{2^{n+1}+1} -\frac{1}{2^{n+1}+2} +\dots -\frac{1}{2^{n+2}} \right) + \dots The Euler-Mascheroni constant is defined by γ = lim N ( H N ln N ) \gamma = \lim_{N \to \infty} (H_{N}-\ln N ) So, taking the limit as n tends to infinity, we get: S = 1 γ S=1-\gamma and A + B = 2 A+B =2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...